2015
DOI: 10.1016/j.jbi.2015.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Combining Fourier and lagged k -nearest neighbor imputation for biomedical time series data

Abstract: Most clinical and biomedical data contain missing values. A patient’s record may be split across multiple institutions, devices may fail, and sensors may not be worn at all times. While these missing values are often ignored, this can lead to bias and error when the data are mined. Further, the data are not simply missing at random. Instead the measurement of a variable such as blood glucose may depend on its prior values as well as that of other variables. These dependencies exist across time as well, but cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 34 publications
0
38
0
Order By: Relevance
“…Up to now, numerous successful researches have been devoted to complete missing data in multivariate time series imputation such as [10,11,[20][21][22][23][24][25][26][27][28]. Imputation techniques can be categorized in different perspectives: model-based or machine learningbased and clustering-based imputation techniques.…”
Section: Classical Multivariate Imputation Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Up to now, numerous successful researches have been devoted to complete missing data in multivariate time series imputation such as [10,11,[20][21][22][23][24][25][26][27][28]. Imputation techniques can be categorized in different perspectives: model-based or machine learningbased and clustering-based imputation techniques.…”
Section: Classical Multivariate Imputation Methodsmentioning
confidence: 99%
“…The results showed that the combination of MICE and RF was more efficient than original methods for multivariate imputation. K-Nearest Neighbors ( -NN)-based imputation is also a popular method for completing missing values such as [11,26,27,[30][31][32]. This approach identifies most similar patterns in the space of available features to impute missing data.…”
Section: Classical Multivariate Imputation Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Concerning the imputation task for multivariate time series, many studies have been investigated using machine learning techniques as Shah et al (2014), Liao et al (2014), Rahman et al (2015) and model techniques such as Raghunathan and Siscovick (1996), Schafer (1997), Van Buuren et al (1999), Raghunathan et al (2001), Royston (2007), Joseph et al (2009), Stuart et al (2009, Lee and Carlin (2010), Spratt et al (2010), Gelman et al (2015, Deng et al (2016). The efficiency of these algorithms is based on correlations between signals or their features, and missing values are estimated from the observed values.…”
Section: Related Workmentioning
confidence: 99%